"I've lost some sleep over It": secondary trauma in the provision of support to older fraud victims - Cross, Cassandra (Canadian journal of criminology and criminal justice, 2017)
The Senior Support Unit (SSU) operates from the Canadian Anti-Fraud Centre and uses volunteers (all seniors themselves) to provide telephone support to older fraud victims across Canada. Many fraud victims have experienced significant trauma, and working with them to assist in their recovery can be difficult. Secondary trauma is well established in other contexts as affecting both professionals and volunteers who work with victims. However, secondary trauma has not been examined in the context of supporting fraud victims. Based on interviews with 21 SSU volunteers, it is argued that there are several indicators of secondary trauma evident in the experiences of the SSU volunteers. This article examines the challenges that exist in supporting fraud victims within a secondary trauma framework. This includes the distressing nature of the calls, maintaining boundaries, repeat victims, and suicidal victims. However, it also describes the coping mechanisms that the SSU volunteers have put in place to enable their continued support, primarily focusing on the positives and seeking collegial support. Despite the trauma associated with helping fraud victims, the SSU has developed a strong and positive culture that supports volunteers in that capacity. The article concludes with what can be learned from the SSU example.